Strength, ductility and cyclic loading performance of plant and animal-based, natural fiber structures - Dimitrios C. Rodopoulos; Nikolaos Karathanasopoulos (Case Studies in Construction Materials)
The current contribution investigates the mechanics of helically-braided, load-bearing structures crafted from plant and animal-based natural materials, including goat hair, coconut, palm, manila (abaca) fibers, and palm leaves. The constituent fibers are subjected to chemical analysis through spectroscopy, while geometric and material density attributes are assessed. Their static and cyclic mechanical attributes are analyzed, identifying primal differences among the fiber types for each loading type case. Manila fiber-based structures yield the highest effective static properties, with peak stress values above 70 MPa and energy absorptions up to 30 J∕mm3, followed by coconut-fiber structures with corresponding values of 33 MPa and 7.3 J∕mm3. These values are approximately an order of magnitude higher that those recorded for animal-fiber-based, helically-braided structures. The associated cyclic loading characteristics differ significantly from the corresponding static properties. Moderate static strength coconut fiber structures exhibit substantially higher hysteresis loss values (above 0.04 J∕MPa after several loading cycles) in comparison to the stiffer, manila-based designs. Furthermore, the ratio of the hysteretic loss energy to the total energy differs, with low-strength palm leaf fiber structures to yield a comparable performance with the high static strength, manila-fiber designs. In all cases, the evolution of the hysteretic energy loss magnitude as a function of the loading cycle is characterized, deriving correlations among the structural composition and the recorded cyclic response performance. Moreover, Ashby-type classifications are conducted with respect to a wide range of natural materials, highlighting the distinctive energy absorption capacity of manila and coconut fiber designs, approaching 1000 kJ∕kg, values that are several times higher than those recorded for metallic helically-braided structures.